Fitness variation in response to artificial selection for reduced cell area, cell number and wing area in natural populations of Drosophila melanogaster - Trotta, Vincenzo (BioMed Central|1, 2007)
BACKGROUND: Genetically based body size differences are naturally occurring in populations of Drosophila melanogaster, with bigger flies in the cold. Despite the cosmopolitan nature of body size clines in more than one Drosophila species, the actual selective mechanisms controlling the genetic basis of body size variation are not fully understood. In particular, it is not clear what the selective value of cell size and cell area variation exactly is. In the present work we determined variation in viability, developmental time and larval competitive ability in response to crowding at two temperatures after artificial selection for reduced cell area, cell number and wing area in four different natural populations of D. melanogaster. RESULTS: No correlated effect of selection on viability or developmental time was observed among all selected populations. An increase in competitive ability in one thermal environment (18°C) under high larval crowding was observed as a correlated response to artificial selection for cell size. CONCLUSION: Viability and developmental time are not affected by selection for the cellular component of body size, suggesting that these traits only depend on the contingent genetic makeup of a population. The higher larval competitive ability shown by populations selected for reduced cell area seems to confirm the hypothesis that cell area mediated changes have a relationship with fitness, and might be the preferential way to change body size under specific circumstances.